Laparoscopy in uterine cervical cancer - Sarrouf, Jorge (2015)
A fundamental principle in assessing the prognosis of cervical cancer is to have information about lymphatic invasion. Imaging techniques have improved during the past years, but the only reliable way to detect lymphatic invasion is the pathologic study of the specimen. The aim of laparoscopic lymphadenectomy is to determine lymphatic nodes, bladder, bowel and abdominal cavity compromise. It can also study the sentinel node. There are two tipes of lymphadenectomy: sampling and radical. Laparoscopy pelvic and paraaortic lymphadenectomy is effective for staging and treatment of gynaecologic cancers. Laparoscopy paraaortic lymphadenectomy has few complications, provides an acceptable number of lymphatic nodes and has a shorter recovery. Also it is useful when extended field radiotherapy is planned for endometrial and cervical cancers.